Determinants of parental vaccine hesitancy in Canada: results from the 2017 Childhood National Immunization Coverage Survey - Ruoke Chen; Mireille Guay; Nicolas L. Gilbert; Eve Dubé; Holly O. Witteman; Hina Hakim (BMC, 2023)
Abstract Background In 2019, the World Health Organization (WHO) designated vaccine hesitancy as one of the ten leading threats to global health. Vaccine hesitancy exists when vaccination services are available and accessible, but vaccine uptake is lower than anticipated. It is often attributed to lack of trust in vaccine safety and effectiveness, or low level of concern about the risk of many vaccine-preventable diseases. This study aimed to examine the sociodemographic factors associated with parental vaccine hesitancy and vaccine refusal in Canada using data from the 2017 Childhood National Immunization Coverage Survey (CNICS). Method The 2017 CNICS was a cross-sectional and nationally representative survey to estimate national vaccine uptake and to collect information about parents' Knowledge, Attitudes and Beliefs (KAB) regarding vaccination. Using the KAB questions, parental vaccine hesitancy (i.e., parental hesitation, delay or refusal of at least one recommended vaccination) and refusal (i.e., unvaccinated children) by sociodemographic factors was estimated using weighted prevalence proportions. A multinomial logistic regression model was fitted to examine associations between parental vaccine hesitancy or refusal and sociodemographic factors among parents of two-year-old children in Canada. Adjusted odds ratios (aOR) of being vaccine-hesitant or vaccine-refusing versus being non-vaccine-hesitant were generated. Results Both unadjusted and adjusted logistic regressions models showed that parents with lower household income (aOR 1.7, 95% CI 1.2-2.5), and those with a higher number of children in the household (aOR 2.2, 95% CI 1.4-3.5) had higher vaccine hesitancy. Conversely, lower vaccine hesitancy was observed among immigrant parents (aOR 0.4, 95% CI 0.3-0.6). In addition, lower household income (aOR 4.0, 95% CI 1.3-12.9), and higher number of children in the household (aOR 6.9, 95% CI 2.1-22.9) were significantly associated with parental vaccine refusal. Regional variations were also observed. Conclusion Several sociodemographic determinants are associated with parental vaccine hesitancy and refusal. The findings of the study could help public health officials and policymakers to develop and implement targeted interventions to improve childhood vaccination programs.